ANOTHER LOOK AT SOVEREIGNTY: Sourcing the Disaster of Neo-liberalism and the Catastrophe of Neo-fascism - Schultz, Walter (Science et Esprit, 2021)
Cornel West, the distinguished public philosopher and Christian advocate for racial, social and political justice, has aptly referred to the 2020 presidential election in the United States as a contest between the disaster of neo-liberalism (Joseph R. Biden Jr., the Democratic Party candidate) and the catastrophe of neo-fascism (Donald J. Trump, the Republican Party incumbent). And Jacques Maritain, the eminent Catholic philosopher of the twentieth century, exposes the modern turn toward the individual, exemplified by the political preoccupation with sovereignty, as the source of this dilemma. Maritain, like postmodern activists Michael Hardt and Antonio Negri, would banish sovereignty from the political lexicon. However, unlike postmodernism, Maritain’s adherence to the absolute engenders a philosophical anthropology and ontology capable of sustaining the rights and equality of each unique human person within the democratic process and community.